Age-specific trends of atrial fibrillation-related ischaemic stroke and transient ischaemic attack, anticoagulant use and risk factor profile in Chinese population: a 15-year study. Issue 9 (26th May 2017) - Soo, Yannie; Chan, Nathan; Leung, Kam Tat; Chen, Xiang-Yan; Mok, Vincent; Wong, Lawrence; Leung, Thomas
Abstract : Background: Prevalence of atrial fibrillation (AF) is increasing globally, and the fivefold increase in stroke risk constitutes significant healthcare burden. Aims: We aim to evaluate the trends of AF-related stroke and transient ischaemic attack (AF-stroke/TIA), prior anticoagulant use and their risk factors in different age groups in Chinese population. Methods: Data were retrieved from the stroke registry at Prince of Wales Hospital. We compared the data at 5-year intervals over a 15-year period (years 1999, 2004, 2009 and 2014). Results: A total of 3894 patients were included, 712 patients had AF-stroke/TIA. Over the 15 years, the total number of ischaemic stroke/TIA fluctuated slightly during the period from year 1999 to 2009, and increased by 21.5% in the year 2014. While AF-stroke/TIA increased continuously with time by 282.1%. Increasing trend of AF-stroke/TIA was observed in all age groups. Absolute growth was highest in patients aged ≥80 years; relative growth was most pronounced in those between 65 and 72 years (>3.5 fold increase). Throughout the 15 years, >70% of AF-stroke/TIA occurred in non-anticoagulated patients, and this proportion increased with age. Increasing trends in both hypertension and ischaemic heart disease were also observed in patients with AF aged ≥73 years. Conclusion: AF-stroke/TIA has increased continuously by >2.5 fold in Chinese population over a 15-year period, with the majority of AF-stroke/TIA occurring in non-anticoagulated patients. Strategic planning is needed to optimise anticoagulant use, particularly non-vitamin K antagonist oral anticoagulants in elderly patients, low-income group and those with ischaemic heart disease requiring concomitant antiplatelet therapy.